2018
DOI: 10.1016/j.jvs.2017.08.098
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of thoracic endovascular aortic repair for chronic aortic dissections

Abstract: TEVAR for cTBD may be performed with acceptable rates of morbidity and mortality. Changes in sac diameter in the midterm are promising. Long-term data are needed to determine whether this approach is durable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…[11][12][13] However, several studies have shown that more extensive stent-graft coverage does not convey significant benefits with regard to either FL thrombosis formation 14,15 or aortic diameter change. 16,17 The present study used the percentage of the stented descending aorta (PSDA), calculated by dividing the length of the stented descending aorta by the total length of the descending aorta, as a novel surrogate of the extent of stentgraft coverage. The association between PSDA and the risk of TAE after TEVAR was examined.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] However, several studies have shown that more extensive stent-graft coverage does not convey significant benefits with regard to either FL thrombosis formation 14,15 or aortic diameter change. 16,17 The present study used the percentage of the stented descending aorta (PSDA), calculated by dividing the length of the stented descending aorta by the total length of the descending aorta, as a novel surrogate of the extent of stentgraft coverage. The association between PSDA and the risk of TAE after TEVAR was examined.…”
Section: Introductionmentioning
confidence: 99%
“…7,21 The approximately 40% female study population in the Valiant Evo trial is very consistent with previous clinical trials although the fraction of women is slightly lower in real-world TEVAR registries where men comprise 70% to 80% of the patient population. 12,22,23 In addition to the large proportion of females in the trials, core laboratory imaging graded 70.9% and 85.7% of the Valiant Evo patients as having severe access artery and high thoracic aorta tortuosity, respectively. Access artery tortuosity can result in a more complicated TEVAR if additional intraoperative procedures such as iliac stenting, or endo-or open iliac conduits become necessary.…”
Section: Discussionmentioning
confidence: 99%
“…14) However, complete false lumen thrombosis in chronic aortic dissection occurs only in 40% to 80% of the patients at the level of the device and in 0%-40% of the patients at the level distal to the device. 15) In a prospective cohort study, VIRTUE registry revealed that patients with subacute dissection (15-92 days) demon- Repeat Surgery for Thoracic Aortic Aneurysm strated a similar degree of aortic remodeling compared to patients with acute dissection (< 15 days). 16) However, the rate of remodeling was poorer in the chronic phase (> 92 days).…”
Section: Discussionmentioning
confidence: 99%